Late Holocene shorelines in East Attica (Greece). - Evelpidou, N.; Karkani, A.; Kampolis, I.; Pirazzoli, P. (International Colloquium 'The Mediterranean Islands", 2015)
Remains of past sea levels, such as tidal notches, benches, beachrocks, etc. may provide valuable information for the investigation of relative sea level changes of eustatic and/or tectonic origin. Tidal notches are usually formed in limestone cliffs in the mid-littoral zone, are well known as precise sea-level indicators and they can attest to the modality of sea level change (rapid or slow) allowing to identify palaeoseismic events. In this framework, this work focuses on the eastern coasts of the Attica Peninsula (eastern Greece) in order to trace the palaeoshorelines of the Upper Holocene through the use of tidal notches and discuss their implication for the interpretation of the recent tectonic history in the area. A submarine geomorphological investigation took place in the coasts of eastern Attica, aiming to identify palaeoshorelines. Former sea-level positions were deduced from emerged and submerged tidal notches. An attempt was made to date past sea level positions, based on 14C datings from sedimentological data of drillings in nearby locations for the submerged tidal notches while one uplifted shoreline was dated with 14C based on a shell collected at a nearby location. Eight fossil shorelines were deduced in the study area; two emerged ones at about +24±6 and +40±6 cm, and six submerged ones at about -22±6 (modern), -40±6, -60±6, -80±6, -130±6 and -460±6 cm. It is worth mentioning that a rather different tectonic behavior may be distinguished between the south (AT1-AT5) and the north (AT10-AT28) part of the study area.